2015
DOI: 10.7205/milmed-d-13-00416
|View full text |Cite
|
Sign up to set email alerts
|

Total Force Fitness: The Military Family Fitness Model

Abstract: The military lifestyle can create formidable challenges for military families. This article describes the Military Family Fitness Model (MFFM), a comprehensive model aimed at enhancing family fitness and resilience across the life span. This model is intended for use by Service members, their families, leaders, and health care providers but also has broader applications for all families. The MFFM has three core components: (1) family demands, (2) resources (including individual resources, family resources, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 95 publications
1
17
0
Order By: Relevance
“…Furthermore, based on the larger collective of research focusing specifically on the benefits derived from father involvement, as well as the detrimental effects of their absence, there is reason to suspect that fathers' resilient coping also has ramifications for youth well‐being (Cabrera, Fitzgerald, Bradley, & Roggman, ; Jeynes, ). Taken together, these findings and existing theoretical evidence suggest that parental coping strategies may represent a pivotal parental characteristic to consider when seeking to gain a better understanding of youth well‐being (Bowles et al., ; Chandra, Martin, et al., ; Huebner et al., ).…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Furthermore, based on the larger collective of research focusing specifically on the benefits derived from father involvement, as well as the detrimental effects of their absence, there is reason to suspect that fathers' resilient coping also has ramifications for youth well‐being (Cabrera, Fitzgerald, Bradley, & Roggman, ; Jeynes, ). Taken together, these findings and existing theoretical evidence suggest that parental coping strategies may represent a pivotal parental characteristic to consider when seeking to gain a better understanding of youth well‐being (Bowles et al., ; Chandra, Martin, et al., ; Huebner et al., ).…”
Section: Introductionmentioning
confidence: 69%
“…These paths were of similar magnitude for mothers and fathers, and a supplementary analysis revealed that these paths were not significantly different (i.e., constraining these two paths did not alter the chi‐square statistic significantly), suggesting that community connections are equally valuable for mothers' and fathers' resilient coping abilities. In line with the ideas of others, it is likely that community connections facilitate the utilization of resources within the community in times of need, thereby resulting in more resilient coping (Bowles et al., ). Even without using community resources, community engagement and sense of community can foster the sense of a “safety net” if needed, thereby promoting confidence in one's ability to manage a difficult situation.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations